THE EFFECT OF APPLICATION OF LEARNING MODELS AND LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES IN SOCIAL STUDIES SUBJECTS - Intan Nur Aini (Edelweiss : Journal Of Innovation In Educational Research, 2023)
The learning process carried out by many teachers today tends to achieve the target curriculum materialand is more concerned with memorizing concepts rather than understanding. This can be seen from thelearning activities in the classroom which are always dominated by the teacher. In delivering material,the teacher usually uses the lecture method in which students only sit, take notes, and listen to what theteacher says and there are few opportunities for students to ask questions. Thus, the learning atmosphereis not conducive so that students become passive. If students are psychologically less interested in thelearning method or model used by the teacher, students will naturally provide psychological feedbackthat is less supportive in the learning process. The indication is that there is a feeling of not havingsympathy for the teacher, not being interested in learning materials, and over time, indifference to thesubject of learning arises. Fun learning can make students dare to try, or do, dare to ask questions, dareto express ideas, dare to question the ideas of others. Therefore the author realizes that the PAKEMlearning model is suitable for improving student learning outcomes. Because the PAKEM learning model(Active, Creative, Effective, and Fun Learning) allows students to do a variety of activities to developskills, attitudes, and understanding of various sources and learning aids including the use of theenvironment so that learning is more interesting, fun and effective.